Pengaruh Return On Total Asset, Debt To Equity Ratio Dan Price Earning Ratio Terhadap Nilai Perusahaan(Study Kasus pada Perusahaan Manufaktur yang Tercatat di Bursa Efek Indonesia) - Jati Prakosa, Drajat; , Dr. H. Syamsudin, M.M (2016)
The purpose of this research is: (1) to analyse the influence of the ROA against the PBV on manufacturing companies listed on the Indonesia stock exchange. (2) to analyse the influence of DER against PBV on manufacturing companies listed on the Indonesia stock exchange. (3) in order to analyze the influence of PER against the PBV on manufacturing companies listed on the Indonesia stock exchange. Hypothesis testing in this study using multiple Linear regression analysis. The data in this study is secondary data derived from the annual financial report of the manufacturing companies listed on the Indonesia stock exchange from 2011 to 2016. Based on the research results of multiple linear regression analysis found that ROA, DER, and PER a positive effect against PBV, both partially mapun simultaneously. The value of the company is diproksi using the PBV can be explained by the ROA, DER, and PER registration of 55.20% and the rest of 44.80% existence illustrates the influence of other variables outside of this research. Keywords: ROA, DER, PER, multiple linear regression, PBV